Analisis Pengaruh Current Ratio, Debt To Equity Ratio, Total Asset Turnover, Net Profit Margin Terhadap Return On Equity pada Perusahaan Properti Dan Real Estate yang Terdaftar di Bursa Efek Indonesia Tahun 2013-2017 - Vonny, Vonny (Jurnal Manajemen Bisnis dan Kewirausahaan, 2019)
In its development, current financial statements are not only used to present the amount of profit that can be obtained in a certain period, but also can show indicators of financial performance of a company. To be able to measure the financial performance of a company, a financial statement analysis is needed, where one type of technical financial statement analysis can be done using financial ratio analysis. Users of financial statements, including shareholders can measure the effectiveness and efficiency of capital management carried out by company management by measuring the size of profitability, namely Return on Equity, which is the dependent variable tested in this study. This study aims to determine how the effect of Liquidity Ratio (Current Ratio), Leverage Ratio (Debt to Equity Ratio), Activity Ratio (Total Asset Turnover) and Profitability Ratio (Net Profit Margin) both partially and simultaneously to Profitability Ratio (Return on Equity). The object of this study is the Property and Real Estate companies listed on the Indonesia Stock Exchange in the period 2013-2017. The determination of the sample used in this study was purposive sampling using multiple regression models. The results of this study indicate that both partially and simultaneously, Current Ratio, Debt to Equity Ratio, Total Asset Turnover and Net Profit Margin have a significant effect on Return on Equity.